2017
DOI: 10.1186/s40759-017-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining parameters and wire vibration in wire electrical discharge machining process

Abstract: Background: Wire Electrical discharge machining (WEDM) has higher capability for cutting complex shapes with high precision for very hard materials without using high cost of cutting tools. During the WEDM process, the wire behaves like a metal string, straightened by two axial pulling forces and deformed laterally by a sum of forces from the discharge process. Major forces acting on the wire can be classified into three categories. The first is a tensile force, pulling the wire from both sides in axial direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…As the variations were very feeble it may have been caused due to wire vibration resulting from sparking. 31,34…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the variations were very feeble it may have been caused due to wire vibration resulting from sparking. 31,34…”
Section: Resultsmentioning
confidence: 99%
“…As the variations were very feeble it may have been caused due to wire vibration resulting from sparking. 31,34 Variation of profile areas at different slant angles Figure 4 shows the variation of areas at different slant angles that were machined from various parameters. It can be observed that each parameter yields different areas although the cutting parameters such as pulse on, servo voltage etc.…”
Section: Effect Of D On Profile Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the debris particles which adhered around the wire also generate high KW. When the wire is running at a higher speed the debris and reinforced particles get discarded from the wire surface and resulted in reduced KW [56]. From the 3D surface graph, it can be seen that KW decreases as tension in the wire increases.…”
Section: Kerf Widthmentioning
confidence: 99%
“…This scheme uses an unusual plan of orthogonal arrays to cram the whole constraint space with petite number of experiments only. In this study, five machining parameters were used as control factors and each parameter was designed to have three levels, denoted 1, 2 and 3 [14,15,16] . According to the Taguchi quality design concept, a L27 orthogonal array table with 27 rows, analogous to the number of experiments as preferred for the experiments and the consequences are presented in Table 3.…”
Section: B Design Of Experiments Based On Taguchi Methodsmentioning
confidence: 99%